-12+9x=7x+18

Simple and best practice solution for -12+9x=7x+18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12+9x=7x+18 equation:


Simplifying
-12 + 9x = 7x + 18

Reorder the terms:
-12 + 9x = 18 + 7x

Solving
-12 + 9x = 18 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-12 + 9x + -7x = 18 + 7x + -7x

Combine like terms: 9x + -7x = 2x
-12 + 2x = 18 + 7x + -7x

Combine like terms: 7x + -7x = 0
-12 + 2x = 18 + 0
-12 + 2x = 18

Add '12' to each side of the equation.
-12 + 12 + 2x = 18 + 12

Combine like terms: -12 + 12 = 0
0 + 2x = 18 + 12
2x = 18 + 12

Combine like terms: 18 + 12 = 30
2x = 30

Divide each side by '2'.
x = 15

Simplifying
x = 15

See similar equations:

| 2x+3-4X+1=6 | | 9y-2(3y-30)=y+80 | | 38+2a+54= | | 2(x+50)-6=4(3x+20) | | 18-25n=10 | | 41000000+b=56000000 | | 5-2x=19-5x | | 2x-4=2x+-2 | | x^2+(x-2)(x-2)=(x-9)(x-9) | | 15x-8=4x+47 | | (3t-2)+6=2 | | 11x+33= | | 7y+x=37 | | 3m-60+3m=2m+84 | | 3x+5y-2x-7y= | | x+3*2x=90 | | 5(5)(g)+5(3)+25=115 | | 7(3+4x)=21 | | 4x-44=4(5x+1) | | 3(c-8)=c+76 | | 3x-2(x-3)=4-(5x-1) | | 47.90=0.045k+6.5 | | 6-6x=6x-10x-6 | | 6+x=4.25 | | 3.14159265359=7x-2y | | 2h^2-2h-1=0 | | 2(6-x)=8 | | -3x-82=8x+50 | | 10r-9=54 | | 3(3x-2)=5x-30 | | 3(k-50)-k=2k+84 | | 2d+97=-d-17 |

Equations solver categories